PUBLIC SPACE: STRUCTURE AND CONSTITUENTS, THEIR FEATURES AND PRINCIPLES - Lukin , Serhii (Theory and Practice of Public Administration, 2020)
The article presents the concept of “publicity”, “public sphere” and “public space”. Public outdoor space is a multidimensional space, where determined by the method of regulation of the society of real interest. Given its specificity, it should be noted that it is not only the space of one generation, it incorporated the traditions of previous generations and it facilitates the transfer of accumulated experience and traditions of others. In the structure of public space occupies a special place in public-political field in which there is a struggle for the right to shape the picture of reality, to determine the degree of relevance of certain issues and to speak on behalf of other agents.The article presents a model of “Euclidean public space” – four-dimensional space, where each dimension should be considered as abstract objects with certain properties, which in some cases can be represented in the form of a planar part of the total concept of “public space”.The basic principles of public space, as principles of functioning of separate components, namely: transparency, objectivity, and democracy in the management of the city, comfort, friendliness, security, development, education, technology, economy, mobility, culture etc. which form an efficient system functioning of the city.Research into public space of the city gives quite comprehensive information about functioning of a society, its values, priorities and orientation, level of integration and development. Therefore, public space is an important and promising object of scientific study. Obviously, in a dynamic and changing modern society, the particular interest of researchers is caused by changes occurring in the social environment – social relations, communities, institutions and the like.Naturally, these changes have a particular impact on the public space, and most of his organization, and on the functional purpose and characteristics of public use. The list of signs of public space, which can be traced to the social changes taking place in urban areas, we consider as one of the steps towards building a methodological Toolkit for the study of social change in the modern city.